The occurrence of quenching cracks in high-carbon tool steel depending on the austenitizing temperature. (October 2018) - Šolić, Sanja; Podgornik, Bojan; Leskovšek, Vojteh
Abstract: Heat treatment has the greatest impact on the microstructure and properties, as well as the residual stresses and dimensional control of steel. Most of the problems that occur in heat-treated parts are attributed to improper heat-treatment practices, deficiency in the used grade of steel, poor part design or part defects. Inappropriate heat-treatment practices include overheating, burning, non-uniform heating, incorrectly selected austenitizing temperature and improper quenching. The formation of cracks during and after the quenching of austenitized steels is a major problem. As the carbon content of steel increases, the tendency to crack increases too. The tendency for quench cracking is also increased with higher austenitizing temperatures. The aims of the research were to determine the cause of the cracks in high‑carbon tool steel and to analyze the influence of the austenitizing temperature on the occurrence and propagation of quenching cracks. The results show that the main cause of quenching cracks is a too high austenitizing temperature caused by poor temperature control. A temperature that is too high leads to excessive austenite grain growth, distinctive grain boundaries with coarser martensite and the presence of retained austenite. On the other hand, the best properties and the absence of quenching cracks occur when C85S steel is quenched from a temperature below the Acm temperature. Highlights: Heat treatment has the greatest impact on the microstructure and properties of steel. Improper heat treatment practices often leads to the formation of the quenching cracks. The cause for the appearance of quenching cracks in high carbon steel was investigated. Quenching should be performed from the properly chosen austenitizing temperature.